Beginning Restorative Activities Very Early: Implementation of an Early Mobility Initiative in a Pediatric Onco-Critical Care Unit - Ghafoor, Saad; Fan, Kimberly; Williams, Sarah; Brown, Amanda; Bowman, Sarah; Pettit, Kenneth L.; Gorantla, Shilpa; Quillivan, Rebecca; Schwartzberg, Sarah; Curry, Amanda; Parkhurst, Lucy; James, Marshay; et al. (Frontiers in Oncology, 2021)
Introduction Children with underlying oncologic and hematologic diseases who require critical care services have unique risk factors for developing functional impairments from pediatric post-intensive care syndrome (PICS-p). Early mobilization and rehabilitation programs offer a promising approach for mitigating the effects of PICS-p in oncology patients but have not yet been studied in this high-risk population. Methods We describe the development and feasibility of implementing an early mobility quality improvement initiative in a dedicated pediatric onco-critical care unit. Our primary outcomes include the percentage of patients with consults for rehabilitation services within 72 h of admission, the percentage of patients who are mobilized within 72 h of admission, and the percentage of patients with a positive delirium screen after 48 h of admission. Results Between January 2019 and June 2020, we significantly increased the proportion of patients with consults ordered for rehabilitation services within 72 h of admission from 25 to 56% (p<0.001), increased the percentage of patients who were mobilized within 72 h of admission to the intensive care unit from 21 to 30% (p=0.02), and observed a decrease in patients with positive delirium screens from 43 to 37% (p=0.46). The early mobility initiative was not associated with an increase in unplanned extubations, unintentional removal of central venous catheters, or injury to patient or staff. Conclusions Our experience supports the safety and feasibility of early mobility initiatives in pediatric onco-critical care. Additional evaluation is needed to determine the effects of early mobilization on patient outcomes.